Clinical Classification in Orthopaedics Trauma (Springer Singapore, 2018)
This book covers common fracture and dislocation classifications for nearly every part of the human body. For each part, it introduces readers to the historical evolution of fracture classifications, as well as the commonly used classifications, with likelihood from high to low. To describe these classifications, the book combines extensive descriptions, tree and schematic diagrams, elegant drawings and detailed radiological images. This structure will help readers recognize the differences between various classifications, and make proper decisions on the basis of their specific research purposes. As such, the book offers a valuable reference guide for orthopedists, radiologists and medical students alike. Editor Yingze Zhang is a surgeon and director of the orthopedic department, The Third hospital of Hebei Medical University, Shijiazhuang, China. He is also the president of the hospital.